Classification of stainless steel and mild steel using vibration technique - Intan Maisarah Abd Rahim (School of Mechatronic Engineering, 2011)
This research presents a development of a material classification scheme with non-destructive testing on the material to classify the material type. This purpose of the research is to implement the non-destructive vibration testing in classifying the type of different materials.